A chromosome-level genome assembly of the Henosepilachna vigintioctomaculata provides insights into the evolution of ladybird beetles. (16th January 2023) - Zhu, Wenbo; Chi, Shengqi; Wang, Yanchun; Li, Haorong; Wang, Zhongkai; Gu, Songdong; Sun, Ting; Xiang, Hui; You, Ping; Ren, Yandong
Abstract: The ladybird beetle Henosepilachna vigintioctomaculata is an economically significant oligophagous pest that induces damage to many Solanaceae crops. An increasing number of studies have examined the population and phenotype diversity of ladybird beetles. However, few comparative genome analyses of ladybird beetle species have been conducted. Here, we obtained a high-quality chromosome-level genome assembly of H. vigintioctomaculata using various sequencing technologies, and the chromosome-level genome assembly was 581.63 Mb, with 11 chromosomes successfully assembled. The phylogenetic analysis showed that H. vigintioctomaculata is a more ancient lineage than the other three sequenced ladybird beetles, Harmonia axyridis, Propylea japonica, and Coccinella septempunctata . We also compared positively selected genes (PSGs), transposable elements (TEs) ratios and insertion times, and key gene families associated with environmental adaptation among these ladybird beetles. The pattern of TEs evolution of H. vigintioctomaculata differs from the other three ladybird beetles. The PSGs were associated with ladybird beetles development. However, the key gene families associated with environmental adaptation in ladybird beetles varied. Overall, the high-quality draft genome sequence of H. vigintioctomaculata provides a useful resource for studies of beetle biology, especially for the invasive biology of ladybird beetles.